Jurymen Seldom Rule Against a Person That They Like: The Relationship Between Emotions Towards a Defendant, the Understanding of Case Facts, and Juror Judgments in Civil Trials - Hannah J. Phalen; Taylor C. Bettis; Samantha R. Bean; Jessica M. Salerno (Behavioral Sciences, 2025)
Legal actors often discuss emotion-based decisions and reasoned evaluation of the facts as distinct and opposite methods through which jurors can reach conclusions. However, research suggests that emotion can have an indirect effect on juror decisions by changing the way that jurors evaluate the facts of the case. In three studies (N = 713, N = 677, N = 651), we tested whether mock jurors’ negative moral emotions towards the defendant predicted their evaluations of unrelated case evidence and in turn their case judgments and whether judicial rehabilitation could reduce this effect. Participants read a civil case and were randomly assigned to either receive judicial rehabilitation or not. Then, they completed measures relating to their negative moral emotions towards the defendant, their agreement with plaintiff and defense evidence, and case judgments. When participants reported increased negative emotions towards the defendant, they agreed more with unrelated plaintiff evidence and less with unrelated defense evidence. In turn, they voted liable more often and awarded more in damages. Judicial rehabilitation did not reduce this effect. This research provides support for the idea that there is a more complicated relationship between emotion and decisions than legal actors suggest. Specifically, negative emotions towards the defendant are associated with a pro-plaintiff evaluation of evidence and pro-plaintiff judgments.